Analisis Pola Pembelian Konsumen pada Toko Sumber Rejeki dengan Pendekatan Data Mining - mu'min, syahri; Editya, Arda Surya (Jurnal Sains dan Teknologi (JSIT), 2025)
This study aims to analyze consumer purchasing patterns at Toko Sumber Rejeki using a data mining approach,specifically the Market Basket Analysis method. In this study, three popular algorithms are used, namely Apriori, FPGrowth, and Eclat to identify associations between products that are often purchased together. The transaction dataanalyzed consists of 200 of purchase data during the period 2023-2024, which is then processed through the preprocessingstage and transformed into a transaction format. The evaluation is carried out based on the support, confidence, and liftmetrics to assess the strength of the association rules generated by each algorithm. In addition, a comparison of algorithmefficiency is seen from the number of rules formed and the computation time required. The results of the study show that allthree algorithms are able to produce rules that are relevant to the needs of the store, but FP-Growth has an advantage inprocessing time efficiency compared to Apriori and Eclat. These findings can be used as a basis for strategic decisionmaking, such as product arrangement and bundling promotions, to increase sales effectiveness.